Temporal variation and environmental drivers of soil heat flux and surface solar radiation in the northern Qinling foothills - Pang, Zhe; Hua, Dongwen; Li, Juan; Li, Jinbin (Frontiers in Environmental Science, 2025)
IntroductionBased on 2021–2023 meteorological data from the northern Qinling foothills.MethodsThis study reveals spatiotemporal variations in soil heat flux (G) and surface solar radiation and their correlations with environmental factors.ResultsResults show soil heat flux (G), measured at 5 cm depth, exhibits a distinct ‘S’-shaped diurnal pattern and seasonal differences, with correlations with surface radiation of R2 = 0.85 (daily scale) and 0.92 (monthly scale) (p < 0.001), respectively. Environmental temperature, soil moisture, and wind speed are significantly positively correlated with G (r = 0.72, 0.24, 0.27, respectively; p < 0.001), while rainfall and atmospheric pressure show negative correlations (r = −0.27, −0.70).DiscussionThese findings provide data support for studying energy exchange in regional soil-vegetation-atmosphere systems.